Fractal Geometry Illustrated Left Atrial Appendage Morphology That Predicted Thrombosis and Stroke in Patients With Atrial Fibrillation - Lei, Chuxiang; Gao, Qi; Wei, Runjie; Li, Qijie; Liu, Xingli; Wu, Lingmin; Yao, Yan; Fan, Hongguang; Zheng, Zhe (Frontiers in Cardiovascular Medicine, 2022)
Background This study aims to correlate the morphological complexity of left atrial appendage (LAA) with thrombosis and stroke in patients with atrial fibrillation (AF). Methods The training cohort consisted of 46 patients with AF (age 55.8 ± 7.2 years, 73.9% men) who were referred for radiofrequency catheter ablation. An independent validation cohort consisting of 443 patients with AF was enrolled for further verification. All patients in the training cohort underwent both transesophageal echocardiography (TEE) and enhanced computed tomography (CT). Fractal dimension (FD) analysis was performed to evaluate the morphological complexity of LAAs quantitatively. Clinical and imaging manifestations, FD of LAAs, and diagnostic accuracy were investigated and compared between patients with AF in both training and validation cohorts. Results In the training cohort, LAAs (n = 22) with thrombi had significantly higher FD than those without thrombi (n = 24) h 0.44 ± 0.07 vs. 2.35 ± 0.11, p = 0.003). Receiver-operating characteristic (ROC) analysis suggested that the diagnostic accuracy of FD combined with a CHA2DS2-VaSc score was significantly higher than that of the CHA2DS2-VaSc score alone in low- to moderate-risk patients with AF (area under the curve 0.8479 vs. 0.6958, p = 0.009). The results were also validated in an independent external validation cohort and demonstrated that increased FD was associated with stroke. Hemodynamic analysis revealed that LAAs with thrombi and high FD were prone to blood stasis and lower blood flow rate. Conclusion LAA morphological complexity is closely associated with thrombosis and stroke in patients with paroxysmal AF. A new risk assessment system combining CHA2DS2-VaSc score and FD has a higher diagnostic accuracy in predicting LAA thrombosis.